2021
DOI: 10.24996/ijs.2021.62.10.8
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Hematological Parameters of Disease Severity in Iraqi Patients with COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is a systemic disease with a substantial impact on the hematopoietic system and hemostasis. Neutrophilia is an early indicator of SARS-CoV-2 infection, while lymphopenia acts as a biomarker of the severity of infection, and the neutrophil-to-lymphocyte ratio (NLR) is the main indicator of cytokine storms. Thus, this study aimed to provide local data about hematological parameters among COVID-19 patients and estimate their correlation with viral load and other factors in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Hence, no significant differences were recorded between them (P>0.05). Wolf et al [2] noticed that the males comprise 54.3-57.3% of hospital admissions and 61.1% of intensive care unit (ICU) patients in China [2].However our study revealed that the male patients comprised 41-46% of hospital admissions and 55.62% of intensive care unit (ICU) in Baghdad. According to Krieger et al [11] males accounted for 62% of in-hospital mortality in Wuhan.…”
Section: 1contrasting
confidence: 63%
See 1 more Smart Citation
“…Hence, no significant differences were recorded between them (P>0.05). Wolf et al [2] noticed that the males comprise 54.3-57.3% of hospital admissions and 61.1% of intensive care unit (ICU) patients in China [2].However our study revealed that the male patients comprised 41-46% of hospital admissions and 55.62% of intensive care unit (ICU) in Baghdad. According to Krieger et al [11] males accounted for 62% of in-hospital mortality in Wuhan.…”
Section: 1contrasting
confidence: 63%
“…The clinical manifestations of SARS-CoV-2 illness are extensive, spanning from silent or mild variants to acute severe pneumonia with serious lung damage and mortality [1]. SARS-CoV-2 intensity and death have been linked to old age, overweight, chronic illnesses and vitamin D deficiency [2]. Furthermore, the intensity of COVID-19 is compounded by an enhanced inflammatory response generated by SARS-CoV-2 which manifests itself as increased levels of inflammatory indicators, mainly pro-inflammatory mediators [3].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of circulating leukocytes are neutrophils, which take part in a variety of immunological and inflammatory processes through phagocytosis, particle formation, cytokine release, and other mechanisms. Patients with COVID-19 may have a bad prognosis because of elevated nytrophil/lymphocyte ratio (NLR) values and low lymphocyte/C reactive protein ratio (LCR) levels that imply an intensified inflammatory process (42) Additionally, the assessed neutrophil or neutrophil-to-lymphocyte ratio (NLR) is thought to be the primary marker of cytokine storms, especially in individuals who are older and have a chronic illness (43,44) .However, the NLR may be related to the severity of the disease, and frequent use of these parameters may help in the assessment of the condition (45) .…”
Section: Neutrophilmentioning
confidence: 99%
“…Nasopharyngeal (NP) or nasopharyngeal (OP) specimen (200μl) was used for viral RNA extraction via the Exiprep TM Plus Viral DNA/RNA Kit (Bioneer, Korea). SARS-CoV-2 infection was detected using a particular real-time reverse transcription-polymerase chain reaction (RT-PCR) on nasopharyngeal swab specimens according to the AccuPower® SARS-CoV-2 Multiplex Real-Time RT-PCR Kit, and recognizing particular E, N, and RdRp gene sequences [7]. Three SARS-CoV-2 highly positive specimens with threshold (Ct) values ranging between (15)(16)(17) and the NGS technique, was used to evaluate samples from three distinct Iraqi areas for the whole genome sequencing.…”
Section: Specimens Collectionmentioning
confidence: 99%